Ejection experience in Serbian Air Force, 1990–2010 - Pavlović, Miroslav; Pejović, Janko; Mladenović, Jovan; Čekanac, Radovan; Jovanović, Dalibor; Karkalić, Radovan; Randjelović, Danijela; Djurdjević, Slaviša (Vojnosanitetski pregled, 2014)
Background/Aim. Ejection injuries are the problem for air forces. The present risk for injuries is still too high, approximately 30–50%. The aim of this study was to determine factors responsible for and contributing to injuries in the Serbian Air Force (SAF) in the last two decades. Methods. All ejection cases in the SAF between 1990 and 2010 were analyzed. The collected data were: aircraft type, ejection seat generation, pilots´ age and experience, causes of ejection, aeronautical parameters, the condition of aircraft control and types of injuries. For ease of comparison the US Air Force Safety Regulations were used to define major injuries: hospitalization for 5 days or more, loss of consciousness for over 5 min, bone fracture, joint dislocation, injury to any internal organ, any third-degree burn, or second–degree burn over 5% of the body surface area. Results. There were 52 ejections (51 pilots and 1 mechanic) on 44 airplanes. The ejected persons were from 22 to 46 years, average 32 years. Major injuries were present in 25.49% cases. Of all the ejected pilots 9.61% had fractures of the thoracic spine, 11.53% fractures of the legs, 3.48% fractures of the arms. Of all major injuries, fractures of the thoracic spine were 38.46%. None of the pilots had experienced ejection previously. Conclusion. Our results suggest that taking preventive measures is obligatory. Namely, magnetic resonance imaging (MRI) scan must be included in the standard pilot selection procedure and procedure after ejection, physical conditioning of pilots has to be improved, training on ejection trainer has to be accomplished, too.
Keywords: aerospace medicine; military personnel; occupational exposure; accidents aviation; wounds and injuries; serbia